Biologically inspired Calixpyrrole ligands for nitrogen activation - Ackley, Casey Anne (Kansas State University, 2020)
Climate change has become one of the most important topics talked about today. A large contributor to climate change is greenhouse gas emissions coming from fossil fuels. Because of greenhouse gas emissions, the Earth’s atmospheric temperature is projected to increase by 1.5 ̊C by the year 2040. Higher temperatures, droughts, forest fires, flooding and other natural disasters are also hypothesized to be consequences of climate change and greenhouse gas emissions. In order to halt these negative impacts, alternative fuel sources must be explored. Ammonia is a favorable choice because it will release nitrogen gas as a byproduct, and it has very similar characteristics to petroleum gas. They are both stored, transported, and handled very similarly, which would make the transition to ammonia fuels much easier. Current production of ammonia is unsustainable so new methods for making this potential fuel are needed. Many scientists have used inspiration from an enzyme called nitrogenase to design catalysts that will produce ammonia from nitrogen. There are several problems with the current nitrogen reduction catalysts. Those problems include very strong acids and reductants for proton and electron sources, as well as, relatively small amounts of ammonia. Changes must be made to increase the viability of nitrogen reduction catalysts. Inspired by literature and nature, a macrocyclic calixpyrrole ligand was synthesized containing a ferrocene backbone to aid in electron transfer. During this synthetic procedure, there was the discovery of two other ligands that could also be useful in creating catalysts for nitrogen reduction.
Keywords: Nitrogen activation; Calixpyrrole ligands; Ligand synthesis